(untitled) (Scripta : English Department Journal, 2026)
This study employed a quantitative correlational design to investigate the relationship between students’ perceptions of English teachers’ teaching methods and their critical and creative thinking skills at SMK Negeri 1 Guguk. The participants of this study were twelfth-grade students (Grade XII). Data were collected from 80 students through questionnaires and tests using a quantitative approach. Data analysis using the Pearson product-moment correlation test revealed a positive correlation between students’ perceptions of teachers’ teaching methods with students’ critical thinking skills, with a correlation value of 0.600 and significance of 0.007, a negative correlation between students’ perceptions of teachers’ teaching methods with students’ creative thinking skills, with a Pearson value of -0.170 and a significance level of 0.048 (<0.05), and a positive correlation between students’ perceptions of teachers’ teaching methods with students’ critical and creative thinking skills, with a Pearson value of 0.273 and a significance level of 0.014 (<0.05). These findings suggest that innovative and creative teaching methods play an important role in developing students’ critical and creative thinking skills. The results indicate that active, student-centered teaching approaches can help students improve their abilities in analysis, evaluation, and problem-solving. Therefore, the study highlights the importance of effective teaching methods in promoting higher-order thinking skills and improving students’ learning outcomes.